2017
DOI: 10.3892/etm.2017.4774
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate attenuates neointimal hyperplasia in a rat model of carotid artery injury by inhibition of high mobility group box 1 expression

Abstract: Epigallocatechin-3-gallate (EGCG) is a kind of polyphenol compound, called catechin, and is extracted from green tea. EGCG has a wide range of biological activities. The present study aimed to evaluate the effect of EGCG on neointimal hyperplasia in a rat model of carotid artery balloon injury and to explore the molecular mechanisms involved. Various experiments were performed to assess the effects of EGCG on thickening of neointima, expression levels of high mobility group box 1 protein (HMGB1) and receptor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In addition, cytoplasmic CIAPIN1 is actively translocated into the nucleus by reactive oxygen species (ROS)-inducing 6-hydroxydopamine in dopaminergic neuronal cells (MN9D) and rat brain (Park et al, 2011). Since vascular injury conditions such as balloon injury and high level of PDGF-BB increased ROS level (Dong et al, 2020;B. Yang et al, 2017), we investigated localisation of CIAPIN1 in vascular injury condition.…”
Section: Interaction Between Ciapin1 and P53 Signallingmentioning
confidence: 99%
“…In addition, cytoplasmic CIAPIN1 is actively translocated into the nucleus by reactive oxygen species (ROS)-inducing 6-hydroxydopamine in dopaminergic neuronal cells (MN9D) and rat brain (Park et al, 2011). Since vascular injury conditions such as balloon injury and high level of PDGF-BB increased ROS level (Dong et al, 2020;B. Yang et al, 2017), we investigated localisation of CIAPIN1 in vascular injury condition.…”
Section: Interaction Between Ciapin1 and P53 Signallingmentioning
confidence: 99%
“…EGCG is the most abundant catechin in green tea and has a variety of biological activities [ 12 ]. A study suggested that EGCG can improve the treatment efficacy of oral nifedipine against severe PE [ 13 ], and EGCG treatment can markedly inhibit the expression of HMGB1 induced by balloon injury [ 16 ]. EGCG can alleviate lung injury by inhibiting the expression of HMGB1 and RAGE [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…EGCG can enhance the endothelial nitric oxide synthase (eNOS) activation and nitric oxide (NO) formation in HUVECs, indicating that EGCG may help improve endothelial functions [ 15 ]. Several studies showed that EGCG can inhibit the expression of HMGB1 [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…downregulates pancreatic RAGE in diabetic mice ( Feng, Hou, Zhu, Zhu, & Jiang, 2019 ); 3) EGCG (2 mg/kg and 4 mg/kg, i.p.) improves restenosis in a rat model of carotid artery balloon injury via inhibiting HMGB1/RAGE and NF-κB activation ( Yang et al, 2017 ); 4) EGCG (75 mg/kg, i.p. 3 times per week) alleviates hyperglycemia, downregulates RAGE expression and reduces advanced glycation end products in mice with high fat diet-induced obesity ( Sampath, Rashid, Sang, & Ahmedna, 2017 ); 5) in patients with type II diabetes, EGCG at doses from 300 to 900 mg/day dose-dependently increases plasma levels of soluble RAGE, a RAGE variant acting as a ligand decoy that competes with RAGE ( Huang et al, 2013 ).…”
Section: Reduction Of Covid-19 Diabetes Comorbidity Risk By Egcgmentioning
confidence: 99%